2020
DOI: 10.5114/aoms.2019.87541
|View full text |Cite
|
Sign up to set email alerts
|

Endocan and a novel score for dyslipidemia, oxidative stress and inflammation (DOI score) are independently correlated with glycated hemoglobin (HbA1c) in patients with prediabetes and type 2 diabetes

Abstract: Introduction: We aimed to examine serum endocan level and the summary involvement of dyslipidemia, oxidative stress (OS) and inflammation by calculation of its comprehensive score (i.e. Dyslipidemia-Oxy-Inflammation (DOI) score) in relation to glucoregulation in subjects with prediabetes and overt type 2 diabetes (T2D). Material and methods: A total of 59 patients with prediabetes and 102 patients with T2D were compared with 117 diabetes-free controls. Glycated hemoglobin (HbA 1c), inflammation, OS and lipid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 33 publications
4
42
0
2
Order By: Relevance
“…Other mechanisms may also be involved in radiation-induced cardiotoxicity. The serum level of endocan has been identified as a risk factor for cardiotoxicity [35,36]. The production of nitric oxide (NO) (both inducible NO and endothelial NO) is another risk factor associated with radiation-induced lethal injury [37], and a recent study shows that the NO pathway plays a key role in ischemia/reperfusion-induced injury [38].…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms may also be involved in radiation-induced cardiotoxicity. The serum level of endocan has been identified as a risk factor for cardiotoxicity [35,36]. The production of nitric oxide (NO) (both inducible NO and endothelial NO) is another risk factor associated with radiation-induced lethal injury [37], and a recent study shows that the NO pathway plays a key role in ischemia/reperfusion-induced injury [38].…”
Section: Discussionmentioning
confidence: 99%
“…The arrest of the lipid peroxidation process coupled with signifi-cant reductions in MDA and PC was reflected in the results of the oxidative stress markers in group D2. Klisic et al [34] calculated a novel summary score (DOI score) using markers of oxidative stress, dyslipidemia, and inflammation, and correlated that score with several diseases.…”
Section: Measurement Of Cell Death Markers In Bloodmentioning
confidence: 99%
“…Although the majority of studies reported increased prooxidant byproducts and decreased antioxidative molecules and antioxidative enzyme activities [11][12][13][14][15][16][17] in many diseases, others reported the opposite, i.e., no changes or even increased antioxidative capacity [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%